What Is the Afterlife Like for Robots? An Experimental Eschatological Sneak Peek - Tretter, Max (Zygon, 2024)
People have always pondered their afterlife. Now, as AI and robotics continue to advance and proliferate, a new question emerges: Is there also some kind of “afterlife” for robots—and how can we envision it? This article seeks to explore these very queries from a Christian perspective. To tackle the initial question, I argue that, following the thoughts of St. Paul and St. Augustine, the whole of creation is sinful and seeks completion, it would be inconsistent to nurture such an all-encompassing hope yet exclude robots from it. From a Christian perspective, we should therefore assume the existence of an afterlife for robots. To decipher how we can envision it, I examine two pop-cultural depictions from the television episode “Zima Blue” and the television series Futurama, questioning whether they provide a fitting image of eschatological completion for robots. This methodological approach allows me to present a spectrum of conceptions of robotic afterlife that, when examined through the lens of systematic theology, appear plausible, offering fresh impetus for eschatological and robophilosophical reflection